Proceedings of the 25th Conference on Computational Natural Language Learning 2021
DOI: 10.18653/v1/2021.conll-1.4
|View full text |Cite
|
Sign up to set email alerts
|

“It seemed like an annoying woman”: On the Perception and Ethical Considerations of Affective Language in Text-Based Conversational Agents

Abstract: Previous research has found that task-oriented conversational agents are perceived more positively by users when they provide information in an empathetic manner compared to a plain, emotionless information exchange. However, users' perception and ethical considerations related to a dialog systems' response language style have received comparatively little attention in the field of human-computer interaction. To bridge this gap, we explored these ethical implications through a scenario-based user study. 127 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The result for anthropomorphism is in line with our expectations of a higher perceived anthropomorphism for social communication considering prior research showing that social robot interactions (Fraune, Oisted, et al, 2020), self-disclosure (Jolley, 2019;Audet and Everall, 2010), content intimacy (Cai et al, 2022;Seeger et al, 2021;Catania et al, 2020), and personal pronouns (Vanderlyn et al, 2021;Seeger et al, 2021;Large et al, 2019;Aggarwal and McGill, 2007) increase anthropomorphism. Despite different levels of anthropomorphism, subjects did accept the robot's recommendation equally often in both communication styles.…”
Section: Anthropomorphismsupporting
confidence: 91%
See 2 more Smart Citations
“…The result for anthropomorphism is in line with our expectations of a higher perceived anthropomorphism for social communication considering prior research showing that social robot interactions (Fraune, Oisted, et al, 2020), self-disclosure (Jolley, 2019;Audet and Everall, 2010), content intimacy (Cai et al, 2022;Seeger et al, 2021;Catania et al, 2020), and personal pronouns (Vanderlyn et al, 2021;Seeger et al, 2021;Large et al, 2019;Aggarwal and McGill, 2007) increase anthropomorphism. Despite different levels of anthropomorphism, subjects did accept the robot's recommendation equally often in both communication styles.…”
Section: Anthropomorphismsupporting
confidence: 91%
“…One study found that the "we" should be emphasized when communicating hospital decisions (Pfaff and Braithwaite, 2020). Another study found that the use of personal pronouns in voice agents contributes to a more personal and natural user experience (Vanderlyn et al, 2021).…”
Section: The Impact Of Social Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality has been found to offer consistency to the interaction [13,46], helping users feel that they are talking to only one person throughout the conversation [62]. Personality also improves the chatbot user experience [62] by enhancing conversational agents' likability and humanness, [65] as a pure information exchange gives way to a more empathetic and self-referencing language style, which is generally preferred and perceived as more realistic, [65] in particular when displaying agreeableness. As observed by [66], displaying humbleness, as well as friendliness, increased users' perceptions of personalisation and social presence, resulting in greater experience satisfaction.…”
Section: Chatbot Gender and Personalitymentioning
confidence: 99%
“…Such effects imply that designers can learn to control, through chatbot personality, how users attribute characteristics to the CA, and use humanness to manage user's expectations and trust. [62] In some cases, specific personality models such as the Big Five, [62,55], Myers-Briggs [65] and DISC theory [32] are used to inform agent design decisions, which in turn determine specific dialogue choices. [54] [27] explored the impact of CA personality on teamwork using a collaborative gaming challenge where the agent displayed two Big Five personality traits, extraversion and agreeableness, utilizing both verbal and nonverbal cues.…”
Section: Chatbot Gender and Personalitymentioning
confidence: 99%